Motivasi Guru Madrasah Ibtida’iyah - Imam Suraji (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2016)
This research is a qualitative study and Phenomenology that aimed to describe the motivation of Madrasa Ibtidaiya teachers in Pekalongan about their teaching activities. Data were collected by in-depth interviews, participant observation, and documentation. Analysis of the data using the interactive model developed by Miles and Hubermen. The result showed that the informants believed that teacher was a blessing (berkah) profession, so they wanted to be a teacher. Therefore, they also said that they hoped to get enough salary (berkat) from their profession. The combination of teachers’ beliefs about the blessings (berkah) in the teaching profession and the hopes to get enough salary (berkat) from it will encourage them to do their job seriously.